Polyurethane foam from oil palm fruit waste: synthesis and characterization of biopolyol and foam properties - Kormin, Shaharuddin (2018)
Oil palm industries generate abundant amount of biomass, which when properly used will not only be able to solve the disposal problem but also can create value added products. The aim of this research is to produce of polyurethane (PU) foams with biopolyols from liquefied oil palm fruit waste (PW). Three parts of oil palm fruit waste (PW): oil palm mesocarp fiber (PM), oil palm shell (PS) and oil palm kernel (PK) was liquefied using liquefaction solvent with sulfuric acid as catalyst was studied. PU foams were prepared from 100 % of PM biopolyol (PMF), incorporation of liquefied PM biopolyol with renewable monomer (PMRF), epoxy (PMEF) and PM fiber filler (PMF1-9) in the presence of dibutyltine dilaurate as a catalyst with water as blowing agent, and silicon oil as a surfactant. The liquefied product and polyurethane foam samples were characterized through the physical, chemical, thermal, mechanical and morphological analysis. The optimal liquefaction conditions were determined to be PW/PEG400 = 1/3, 5 % acid loading, and liquefaction at 150 °C for 120 min. The results revealed that more than 50 % of the oil palm fruit waste converted into liquefied product. The GC-MS analysis showed that the chemical components of phenol and its derivatives, organic acids, hydrocarbon, ester, benzene groups and alcohols. FTIR spectroscopy analysis demonstrated the formation of urethane linkage in liquefied PW biopolyol which suitable for the production of PU foams. Meanwhile, In terms of the thermal properties, the improved thermal insulation properties were achieved at a composition of PMF foams. PMF foams showed higher compression strength (61.41 kPa) and tensile strength (117 kPa). In DMA result, the higher crosslinking density (33.17 M/m3) and crosslinking interaction (NHC(O)O) in PU foam was determined. SEM revealed the exfoliated structure of PU foams and indicated the cells within the obtained foams are closed cells. The properties of the PU foam were indicating that the liquefied PM biopolyol from a solvolysis liquefaction could be successfully applied to fabricate PU foam products as a substitute for industrial foams with lower cost.